2013
DOI: 10.1016/j.jacc.2013.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bariatric Surgery on Human Small Artery Function

Abstract: ObjectivesThe aim of this study was to investigate the effects of bariatric surgery on small artery function and the mechanisms underlying this.BackgroundIn lean healthy humans, perivascular adipose tissue (PVAT) exerts an anticontractile effect on adjacent small arteries, but this is lost in obesity-associated conditions such as the metabolic syndrome and type II diabetes where there is evidence of adipocyte inflammation and increased oxidative stress.MethodsSegments of small subcutaneous artery and perivascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(51 citation statements)
references
References 35 publications
3
41
0
7
Order By: Relevance
“…2009; Aghamohammadzadeh et al. 2013). However, in obese patients the ability of PVAT to release adiponectin and thus ameliorate constriction is lost; and this has been proposed as a potential mechanism contributing to the development of obesity related hypertension (Gao 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009; Aghamohammadzadeh et al. 2013). However, in obese patients the ability of PVAT to release adiponectin and thus ameliorate constriction is lost; and this has been proposed as a potential mechanism contributing to the development of obesity related hypertension (Gao 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a follow‐up study suggested that functional recovery of PVAT following bariatric surgery may be in part due to restoration of adiponectin in the PVAT itself (Aghamohammadzadeh et al. 2013). Adiponectin is a 30kD protein which is released exclusively from adipocytes, and traditionally has been studied in relation to its beneficial anti‐inflammatory and metabolic effects, thought to be mediated through activation of AMP Kinase (Iwabu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Согласно данным ряда исследований, в периваску-лярной жировой ткани пациентов после бариатриче-ских операций наблюдается постепенное уменьшение размера адипоцитов, снижение уровня воспаления, восстановление антиконтрактильных свойств и увели-чение концентрации оксида азота и адипонектина [42].…”
Section: периваскулярная жировая ткань при ожиренииunclassified
“…In addition, PVAT produces transferable vasoactive substances including adipocyte-derived relaxing factors and adipocyte-derived contractile factors (2). The effect of PVAT on arterial reactivity has been examined in human small arteries obtained from subcutaneous adipose tissue biopsies using wire myography (3, 4). PVAT-containing arteries displayed a blunted response to vasoconstrictor agonist stimulation compared to arteries without PVAT from healthy lean subjects.…”
Section: Introductionmentioning
confidence: 99%
“…PVAT-containing arteries displayed a blunted response to vasoconstrictor agonist stimulation compared to arteries without PVAT from healthy lean subjects. Importantly, the anti-contractile effect of PVAT was lost in arteries taken from subjects with metabolic syndrome (3, 4). Obese subjects tend to have lower levels of serum 25-hydroxyvitamin D (25(OH)D) (5).…”
Section: Introductionmentioning
confidence: 99%